Probiotic Supplementation for Periodontal Diseases - An Umbrella Review - Hunny Sharma; Manisha Ruikar; Swati Verma (Indian Journal of Dental Research)
Periodontal disease is a common condition caused by bacterial plaque that damages the supporting structures of teeth. Therefore, to manage periodontal disease, probiotic supplementation has emerged as a potential adjunct therapy. This umbrella review aims to summarize the primary findings, conclusions, and recommendations of systematic reviews and meta-analyses published on the effect of probiotics in treating periodontal disease. A systematic review of the literature was undertaken in four databases, i.e., MEDLINE, Embase, Cochrane Central, and Google Scholar using MeSH terms like ‘Probiotic*,’ ‘Prebiotic*,’ ‘Bifidobacterium,’ ‘Lactobacillus,’ and ‘Periodontitis,’ along with keywords like ‘synbiotic*,’ ‘Systematic review*,’ or Meta-analysis. The AMSTAR-2 tool was used to assess the quality of the included reviews once data were retrieved. A total of 22 systematic reviews and meta-analyses published in the last decade were reviewed, and probiotics were found to have potential benefits in reducing Bleeding on Probing (BOP), Probing Pocket Depth (PPD), and gaining Clinical Attachment Level (CAL) in individuals with periodontal disease. However, there is mixed evidence on the effectiveness of probiotics in reducing gingival inflammation (GI) and dental plaque, and further research is needed to understand the mechanisms of action and potential health benefits of probiotics. The findings of this review suggest that probiotics as an adjunct treatment approach may have potential benefits for managing periodontal disease specially in terms of BOP, PPD, and CAL. However, they should not replace conventional treatments like scaling, root planing, and regular dental hygiene, which are essential for effective care.